Espécies fitorremediadoras em solos hipersalinos do estuário no Rio Apodi-Mossoró (RN) - Clemente, Maria Isabela Batista (2021)
Hypersaline environments are places that have a high natural potential, favoring important ecological and economic services. Phytoremediation is a technique that uses plants that can sequester salts or immobilize pollutants in the soil. This study aimed to evaluate the phytoremediation capacity of halophyte species to Batis maritima L. and Sesuvium portulacastrum L., in hypersaline soils of the Apodi-Mossoró river estuary. Collections were carried out at three points along the Apodi-Mossoró River estuary in the coastal region of Costa Blanca Potiguar. To determine the soil and species collection units, the estuary was subdivided into beginning area (A1), middle area (A2) and end area (A3). Having a completely randomized design in a split-plot scheme, the plots being collected from the soil and the species Batis maritima L. (E1) and Sesuvium portulacastrum L. (E2) the subplots, with 3 replications and 4 experimental units. The treatments consisted of two factors, the first: soil from hypersaline areas collected in A1, A2 and A3 at a depth of 0-20 cm; the second factor corresponds to the two species (E1 and E2), totaling 6 treatments, and each treatment consisted of 4 experimental units within each repetition. The variables analyzed in the plants were, Na+, Cl-. In soils, the following variables were evaluated: pH, CEes and RAS, both in the saturation extract, exchangeable Na+, CTC and PST; and the heavy metals in the soil and in the plant were: Iron (Fe+3); Manganese (Mn+2); Nickel (Ni+2); Cadmium (Cd+2) and Lead (Pb+2). According to the obtained results, it was verified that the halophyte species Batis maritima L. and Sesuvium portulacastrum L., presented a positive correlation of Cl- with Na+ and the analyzed heavy metals. It was observed that species E1 and E2 have a potential to support Na+ concentrations in the field of 16,128 mg/dm3. In area A1, both species presented higher values of Na+, Cl-, Fe+3, Mn+2, Cr+3, Cd+2, Ni+2 and Pb+, being tolerable to environments contaminated with heavy metals. Based on this study, the species are tolerant to heavy metals and adapted to an environment with high salinity, being suitable for phytoremediation, specifically phytoextraction for the recovery of soils affected by salts and heavy metals